Analisis Penerapan Strategi Marketing Mix Syariah dalam Meningkatkan Minat Beli Konsumen pada Produk Todays Donut di Kota Bandung - Majid, Muhammad Ilham; Safar, Mira Purnamasari (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study analyzes the application of sharia marketing mix strategies on Donut Todays products and its impact on consumer buying interest. Using the Kotler framework, product aspects, prices, placement, promotion, people, processes, and physical evidence are integrated with the theory of buying interest to identify four types of interest: transactional, references, preferences, and exploratively. The view of Imam Al-Qurthubi and Ibn Al Manzhur is used to understand the principles and values of sharia. The research method is an analytical descriptive qualitative with data collection techniques through interviews, observation, and documentation regarding the marketing mix strategy of sharia to donut and consumer reviews. The results showed the success of Todays Donut in implementing sharia marketing mix, focusing on product quality and halalness, appropriate pricing, strategic store placement, and promotion through social media. Criticism does not stop buying interest, because product quality and responsiveness to feedback are key. In conclusion, Todays Donut succeeded in applying sharia marketing mix successfully, maintaining product quality, appropriate prices, and adaptive sales. Focus on quality, responsiveness to feedback, and consistency can increase consumer buying interest in Todays Donut.